Chronic scrotal pain may lead to reduced sexual function and interest, while sexual activity may worsen chronic scrotal pain: “double jeopardy” - Aljumaily, Aosama; Al-Khazraji, Hind Abdul Jaleel; Gordon, Allan; Lau, Susan; Jarvi, Keith Allen (Translational Andrology and Urology; Vol 7, Supplement 1 (March 14, 2018): Translational Andrology and Urology1, 2018)
Background: While it is recognized that chronic pain may adversely impact sexual function and activity in men and we also recognize that sexual activity may worsen the pain for men with chronic scrotal pain (CSP), the effect on sexual functioning and conversely the impact of sex on CSP has not previously been documented. Methods: Retrospective analysis of a prospectively collected database. Results: From Feb 2014 to Sep 2015, a total of 128 men presenting for assessment of CSP completed all or parts of a standardized questionnaire. Overall 60% (69/116) of the men felt that the CSP had kept them either a “lot” or “some” of the time from sexual activity and 64% (27/43) had evidence of decreased erectile performance. Those with more severe pain (analog pain scores 7–10/10) had more significant sexual dysfunction than those with less severe pain, with 54% (45/83) vs. 0% (0/33, P